1982
DOI: 10.1001/archderm.118.4.244
|View full text |Cite
|
Sign up to set email alerts
|

Reduced histamine reaction in atopic dermatitis

Abstract: Vascular reactivity to intracutaneously injected histamine phosphate was examined in both the normal and affected skin of 50 patients with atopic dermatitis and 30 patients with allergic contact dermatitis. Reduced histamine reactions occurred consistently in the slightly lichenified skin of patients with atopic dermatitis and in skin sites of allergic contact dermatitis. The normal skin of patients with atopic dermatitis usually showed normal erythematous reactions to intracutaneously injected histamine. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…172 Studies have shown that AD patients had reduced itch sensations with intracutaneously injected or iontophoretically applied histamine when compared with healthy subjects. 173,174 Therefore, it is no surprise that oral nonsedating antihistamines are not very effective against itch in AD. An evidence-based review of multiple randomized, placebo-controlled trials reported little objective evidence for an antipruritic effect of antihistamines in AD.…”
Section: Systemic Antipruritic Agentsmentioning
confidence: 99%
“…172 Studies have shown that AD patients had reduced itch sensations with intracutaneously injected or iontophoretically applied histamine when compared with healthy subjects. 173,174 Therefore, it is no surprise that oral nonsedating antihistamines are not very effective against itch in AD. An evidence-based review of multiple randomized, placebo-controlled trials reported little objective evidence for an antipruritic effect of antihistamines in AD.…”
Section: Systemic Antipruritic Agentsmentioning
confidence: 99%
“…Equally, the increased reactivity to alpha-adrenoceptor stimulation, inferred from in vitro studies (Szentivanyi et al, 1980), does not appear to have an in vivo counterpart in the cutaneous vessels of patients with atopic eczema. Decreased flare responses to intracutaneous histamine in atopic eczema have been previously reported (Eyster, Roth & Kierland, 1952;Michaelsson, 1970) and this phenomenon may be secondary to eczematous inflammation (Uehara, 1982).…”
Section: Discussionmentioning
confidence: 58%
“…The quantity of intercellular edema and mononuclear cell infiltrates varies according to the activity of the process at time of biopsy. Early lesions of pruriginous papules in atopic dermatitis often show an eczematous change at the hair follicle (49). Thus, it should be emphasized that skin manifestations of atopic dermatitis histologically resemble those of acute or chronic allergic contact dermatitis.…”
Section: Immunological Abnormalitiesmentioning
confidence: 99%